Smart concept design based on recessive inheritance in complex electromechanical system. (January 2020) - Zhang, Peng; Nie, Zifeng; Dong, Yafan; Zhang, Zhimin; Yu, Fei; Tan, Runhua
Abstract: Due to the substantial increase in users demand, the scale of complex electromechanical systems is rapidly enlarging when systems are rapidly merging, and the complexity of the system has been greatly increased. Even if the original system is running well, singular phenomena often occurs in the process of complex electromechanical systems integration, which leads to the failure of the functional requirements of the new generation of products. In the face of the singular phenomena of complex electromechanical systems, traditional solutions focus more on solving the problems existing in the current complex electromechanical systems, and do not deeply study the root causes of the singular phenomena in the design process of complex electromechanical systems. The singular phenomena of system has high concealment and is not easy to be detected at the design stage, and similar singular phenomena will appear repeatedly in multiple generations of the same product. These characteristics are very similar to the characteristics of recessive inheritance of biological systems. Therefore, the paper will compare complex electromechanical systems with biological systems, and propose a recessive inheritance mechanism of complex electromechanical systems that can be used in smart concept design by introducing the recessive inheritance mechanism of biological system into the complex electromechanical system design process. First, use function trimming to build a functional gene for new complex electromechanical systems. Second, combine the Length and Time dimension chart (L-T chart) and Computer Aided Innovation (CAI) to find the recessive parameters that may exist in the design of the new generation system and analyze the possible coupling phenomena between the recessive parameters. Then, using the Invention Problem Solving Theory (TRIZ) tools to solve the coupling relationship between recessive parameters to reduce the possibility of singular phenomena in the new generation system, forming a new generation of complex electromechanical system smart concept design theory framework. Finally, for the design example of the new generation of energy-saving surface platform, the proposed method is used to determine the design scheme, establish a 3D model and verify the feasibility and scientificity of the theory by Ansys analysis.